Auditor attributes and their association with audit fees in Australia: an empirical study - Singh, Harjinder (Curtin University, 2010)
This study investigates the existence of cartel pricing and anticompetitive behavior by the Big4 international providers of auditing services (resulting from the halving in the number of such providers from the Big8 to Big4). Increased audit market concentration, both globally and in Australia, together with the focus by the Big4 in servicing primarily large clients, raises concern about a lessening of competition in the audit marketplace. Using both a composite and dis-aggregated measure for auditor attributes (namely, auditor reputation, industry specialization, provision of non-audit services and auditor tenure), this study provides a comprehensive analysis of the association between four pivotal auditor attributes and the quantum of audit fees and changes in audit fees paid by Australian publicly listed firms during a five-year time frame.The final usable sample includes 600 firm-year observations as data points for the 2001, 2003 and 2005 calendar years (200 firm-years for each year in the aforementioned observation window) and is obtained entirely from publicly available sources, specifically annual reports. Main results from both cross-sectional and longitudinal multivariate analysis indicate that there is no significant association between the four auditor attributes utilized in this study with both audit fees and variation in audit fees. Robustness and sensitivity testing completed also largely support the non-significance of the association between both constructs. This study, therefore, finds no evidence of cartel pricing and anti-competitive behavior by Big4 auditors resulting from increased audit market concentration. Results from this study have clear implications for regulators, investors, scholars, corporate management/firms and auditors.